“CHALLENGES IN TEACHING AND LEARNING OF SOCIAL SCIENCE –THE DUAL PERSPECTIVE” - Bhatnagar, Roli (PEOPLE: International Journal of Social Sciences, 2018)
The paper presents an overview of prevailing pedagogic practices of social science in India. It also offers an understanding of the obstacles in achieving an effective system of student-teacher interaction in actual humanities classroom which appear as hindrance in the achievement of optimal results. In this study, interview technique is used as qualitative research method and utilized as a means of data collection. For this purpose, interviews were conducted with the teachers as well as the students in the humanities study group. This provided us with the dual perspective on the issue, both from the teachers as well as the student point of view. The analysis of teachers’ interview revealed that the teaching of social science is a reflection of teacher’s own biases and beliefs; dominated by deficit model of thinking and learning. Against this backdrop the paper tries to find a solution to the problem associated with the issue of objectivity in teaching Social Science. The student interviews on the other hand proved as a resource to find the problems faced by them in understanding the various themes dealt by the teachers in the classroom. Hence, the dual perspective has helped us in understanding the problem from both the sides. This study tries to find the gaps that exist between the knowledge imparted by the teachers and the understanding developed by the students in this process.